Distance learning trough [sic] problems: presentation and analysis of a training system. - Dury C (Recherche en Soins Infirmiers, 2004)
This article presents and analyses a training system aiming at acquiring skills in nursing cares. The aims followed are the development:- of an active pedagogic method: learning through problems (LTP);of the interdisciplinary and intercultural approach, the same problems being solves by students from different disciplines and cultures ;of the use of the new technologies of information and communication (NTIC) so as to enable a maximal 'distance' cooperation between the various partners of the project.The analysis of the system shows that the pedagogic aims followed by LTP are reached. The pluridisciplinary and pluricultural approach, to be optimal, requires great coordination between the partners, balance between the groups of students from different countries and disciplines, training and support from the tutors in the use of the distance teaching platform.